2012
DOI: 10.1371/journal.pone.0039152
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Spatio-Temporal Pattern of the Mammalian Target of Rapamycin (mTOR) Activation in Temporal Lobe Epilepsy

Abstract: Growing evidence from rodent models of temporal lobe epilepsy (TLE) indicates that dysregulation of the mammalian target of rapamycin (mTOR) pathway is involved in seizures and epileptogenesis. However, the role of the mTOR pathway in the epileptogenic process remains poorly understood. Here, we used an animal model of TLE and sclerotic hippocampus from patients with refractory TLE to determine whether cell-type specific activation of mTOR signaling occurs during each stage of epileptogenesis. In the TLE mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 43 publications
4
65
0
Order By: Relevance
“…There is PI3K-and Akt-dependent mTOR activation in a rat hippocampal organotypic culture model of posttraumatic epilepsy, and inhibition of PI3K, mTOR, or both (using a dual inhibitor) mitigated ictal activity and cell death (Berdichevsky et al 2013). Enhanced mTOR activation is found in human temporal lobe epilepsy specimens (Sha et al 2012;Sosunov et al 2012), and a recent study showed enhanced mTOR signaling in a variety of epilepsy-associated structural lesions including mesial temporal sclerosis, FCD type IIIa, FCD type IIIc, and Rasmussen's encephalitis (Liu et al 2014). Enhanced mTOR signaling in neurons is associated with alterations in dendritic morphology, changes in dendritic spine density and structure, and diminished long-term depression, all of which can be linked to enhanced excitability and diminished seizure threshold (for comprehensive review, see Lasarge and Danzer 2014).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 95%
See 1 more Smart Citation
“…There is PI3K-and Akt-dependent mTOR activation in a rat hippocampal organotypic culture model of posttraumatic epilepsy, and inhibition of PI3K, mTOR, or both (using a dual inhibitor) mitigated ictal activity and cell death (Berdichevsky et al 2013). Enhanced mTOR activation is found in human temporal lobe epilepsy specimens (Sha et al 2012;Sosunov et al 2012), and a recent study showed enhanced mTOR signaling in a variety of epilepsy-associated structural lesions including mesial temporal sclerosis, FCD type IIIa, FCD type IIIc, and Rasmussen's encephalitis (Liu et al 2014). Enhanced mTOR signaling in neurons is associated with alterations in dendritic morphology, changes in dendritic spine density and structure, and diminished long-term depression, all of which can be linked to enhanced excitability and diminished seizure threshold (for comprehensive review, see Lasarge and Danzer 2014).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 95%
“…Despite the known association between focal MCD and intractable seizures, distinguishing the differential contributions of altered brain structure, the effects of mutations on downstream gene, and protein expression, mTOR hyperactivation to epileptogenesis has been a challenge (see Aronica and Crino 2013). Although enhanced mTOR signaling is detected in knockout mouse models of mTOR regulatory genes associated with spontaneous seizures (e.g., Tsc1, Tsc2, Pten), hyperactive mTOR signaling is also found in animal models of seizures such as kainate treatment (Zeng et al 2009;Sha et al 2012) or electrical brain stimulation (van Vliet et al 2012) in the absence of structural changes in the neocortex. Enhanced mTOR activation has been linked to mouse models of infantile spasms (see Raffo et al 2011) and seizures induced in a hypoxia model lead to enhanced expression of genesencoding components of the mTOR pathway (Theilhaber et al 2013).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 99%
“…In a mouse model of TLE and in patients with sclerotic hippocampus, the mammalian target of rapamycin (mTOR) signaling pathway was hyperactivated in dispersed granule cells, indicating that mTORC1 activity is involved in GCD induced by epileptic insults (Sha et al, 2012;Shima et al, 2015). In addition, mTOR deactivation due to RA treatment significantly reduces spontaneous recurrent seizures (Huang et al, 2010;Zeng et al, 2009).…”
Section: Inhibitory Effects Of Eug On Ka-induced Mtorc1 Activation Inmentioning
confidence: 99%
“…Recently, accumulating evidence has suggested that the mTOR pathway is closely associated with epilepsy. Sha et al [25] found that significant activation of mTOR exists in MTLE animal models and patients with drug resistance and hippocampal sclerosis (HS). Meanwhile, we have found that IL-1β expression is increased in the MTLE process [16,17] , whether the correlation exists between IL-1β and mTOR, as well as their role in the pathogenesis of MTLE, is unclear.…”
Section: Introductionmentioning
confidence: 99%